Réponses

2013-09-04T17:31:12+02:00
Bonjour,

1)On utilise l'identité remarquable (a+b)² = a²+2ab+b² :
f\left(x\right) = \left(2x+5\right)^2-9x^2\\
f\left(x\right) = \left(2x\right)^2+2\times 2x\times 5 +5^2 -9x^2\\
f\left(x\right) = 4x^2+20x+25 - 9x^2\\
f\left(x\right) = -5x^2+20x+25

2)On remplace x par sa valeur :
f\left(0\right) = -5\times 0^2 +20\times 0 +25\\
f\left(0\right) = 25\\
\\
f\left(2\right)= -5\times 2^2 +20\times 2 +25\\
f\left(2\right) = -5\times 4 +20\times 2 +25\\
f\left(2\right) = -20+40+25\\
f\left(2\right) = 45